SAT0327 B Cell-Bound Complement Activation Products in The Diagnosis and Monitoring of Systemic Lupus Erythematosus. (15th July 2016) - Beckmann, J.; Bartholomä, N.; Venhoff, N.; Henneke, P.; Janda, A.; Salzer, U.
Abstract : Background: Systemic lupus erythematosus (SLE) is a complex autoimmune disease characterized by diverse pathogenic autoantibodies and clinical phenotype. Laboratory monitoring of complement activation products (CAP; C3a, C5a, C3d, C4d) is commonly used in diagnosis and follow up. CAP bound to cellular surfaces (CB-CAP) analysed by flow cytometry offer a relatively novel approach to study complement turnover in SLE. Objectives: We evaluated the significance and usability of cell bound CAP in monitoring complement turnover in a whole blood staining approach, comparing cell bound CAPs on different leucocyte subpopulations with conventional complement and disease activity parameters. Methods: CAP bound to lymphocyte subpopulations were analysed by flow cytometry, compared to serological complement and other SLE activity parameters determined by nephelometry, rocket electrophoresis and ELISA. Results: We have analysed CB-CAPs bound to lymphocytes in 50 adult patients with SLE. B-cells and CD4+ T-cells of SLE patients showed significantly higher levels of cell-surface-bound C4d compared to controls. C4d bound to B-lymphocytes was inversely correlated with serum levels of C4 (r = -0.309, p=0.013) and C3 (r= - 0.356, p=0.004) reflecting complement decay. In addition, B-cell C4d showed a significant positive correlation with anti-dsDNA antibody levels (r =0.574, p<0.001) and plasma C3d (r =0.319, p=0.009) thereby corresponding to disease activity. CB-CAPs were stable over 24 hours after blood drawing thus offering more flexibility in sample handling than conventional complement turnover assays. Conclusions: Our data show that CB-CAP measurement correlates with established disease activity markers, and given its easier handling, is of possible utility in routine diagnostic and monitoring of patients with SLE. A multicentre study for evaluation of this method in a cohort of paediatric patients is planned. Disclosure of Interest: None declared